DNA-RNA Hybrid (R-Loop): From a Unified Picture of the Mammalian Telomere to the Genome-Wide Profile - Minoo Rassoulzadegan; Ali Sharifi-Zarchi; Leila Kianmehr (Cells, 2021)
Local three-stranded DNA/RNA hybrid regions of genomes (R-loops) have been detected either by binding of a monoclonal antibody (DRIP assay) or by enzymatic recognition by RNaseH. Such a structure has been postulated for mouse and human telomeres, clearly suggested by the identification of the complementary RNA Telomeric repeat-containing RNA “TERRA”. However, the tremendous disparity in the information obtained with antibody-based technology drove us to investigate a new strategy. Based on the observation that DNA/RNA hybrids in a triplex complex genome co-purify with the double-stranded chromosomal DNA fraction, we developed a direct preparative approach from total protein-free cellular extract without antibody that allows their physical isolation and determination of their RNA nucleotide sequence. We then define in the normal mouse and human sperm genomes the notion of stable DNA associated RNA terminal R-loop complexes, including TERRA molecules synthesized from local promoters of every chromosome. Furthermore, the first strong evidence of all telomeric structures, applied additionally to the whole murine sperm genome compared to the testes, showed reproducible R-loop complexes of the whole genome and suggesting a defined profile in the sperm genome for the next generation.